From the household to the factory : sex discrimination in the Guatemalan labor force - Sunderland, Judith (Human Rights Watch, 2002)
Recommendations -- International standards and Guatemalan law -- Background -- Gender-specific labor rights violations in the domestic work and maquila sectors -- Response of the Guatemalan government -- Conclusion.